Total 5‐mm port approach: a feasible technique for both elective and emergency laparoscopic cholecystectomy. Issue 11 (24th April 2018) - Bender, Kyle; Lewin, Joel; O'Rourke, Harriet; Hugh, Freya C.; O'Rourke, Nicholas; Hugh, Thomas J.
Abstract : Background: The laparoscopic approach is considered the standard of care for cholecystectomy. Attempts to minimize incisions with single site and natural orifice approaches have shown promise but also have limitations. Technological advances have facilitated decreased port size, which may have a variety of benefits. The aim of this study was to determine the feasibility of an all 5‐mm port approach for patients undergoing both elective and emergency laparoscopic cholecystectomy. Methods: A consecutive series of laparoscopic cholecystectomies at three different hospitals using all 5‐mm ports was prospectively evaluated. Recorded outcomes included operative findings, procedural difficulties, the need to extend the umbilical incision during extraction, operative time, length of stay and post‐operative complications. Results: A total of 101 patients were included and all had a successful cholecystectomy without the need for additional ports. The umbilical incision was extended for gallbladder extraction in 29 (29%) patients. Eight (8%) patients experienced minor post‐operative complications and there were no major complications. Cholangiography was performed in 98% of cases and three patients underwent successful common bile duct exploration without requiring additional ports. In a small number of cases, there was difficulty with the quality of the view through the 5‐mm laparoscope but this was rectified by removing old or damaged laparoscopes from the circulating stock. Conclusion: This study demonstrates that laparoscopic cholecystectomy using all 5‐mm ports is both feasible and safe, and is comparable to published outcomes after conventional laparoscopic cholecystectomy. Further work is needed to determine whether this approach can also improve short‐ and long‐term outcomes.